Effect of compaction, delayed sealing and aerobic exposure on maize silage quality and on formation of volatile organic compounds. (19th April 2017) - Brüning, D.; Gerlach, K.; Weiß, K.; Südekum, K.‐H.
Abstract: Physical and management factors, such as compaction and sealing, greatly influence the outcome of forage conservation. This study aimed to determine the effects of compaction, delayed sealing and aerobic exposure after ensiling on maize silage quality and on formation of volatile organic compounds. Whole‐crop maize (277 g/kg dry matter [DM]) in 120‐L plastic silos was compacted at either high or low density, and sealed immediately or with delay at 2 days or 4 days post‐filling (six replicates each). After ensiling for at least 175 days, the silages were exposed to air for 6‐day intervals and sampled at 2‐day intervals. A delay in sealing caused an increase in yeast counts and a decline of up to 65% in water‐soluble carbohydrates before ensiling. Sealing the silos after 4 days caused DM losses of up to 11%. Delayed sealing promoted the formation of ethyl esters at silo opening. A 4‐day delay in sealing resulted in the lowest aerobic stability. Aerobic exposure led to considerable changes in silage composition, a loss in feed value and, finally, spoilage. This study indicates that maize silage quality is adversely affected by low compaction, delayed sealing and aerobic exposure.